Best Answer

Solving equations in three unknowns (x, y and z) requires three independent equations. Since you have only one equation there is no solution.

The equation can be simplified (slightly) by dividing through by 4 to give:

x + 2y + 3z = 11

Q: Solve the equation 4x plus 8y plus 12z equals 44?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-99 = 12z - 3(6)zSimplifying the expression, we have:-99 = 12z - 18z = -6zDivide by -6:z = 16.5Or, if you meant 3 6 as the number, we have:-99 = 12z - 36zSimplify:-99 = -24zDivide by -24:z = 4.125

x=3y y=4z x=12z x+y+z=z+4z+12z=153 now you have the answer

If you mean: 2x-5y+2z = 16 and 3x+2y-3z = -19 and 4x-3y+4z = 18 then the solutions are found as follows:- 3(2x-5y+2z = 16) => 6x-15y+6z = 48 2(3x+2y-3z = -19) => 6x+4y-6z = -38 Adding the above: 12x-11y = 10 thus eliminating z 4(3x+2y-3z = -19) => 12x+8y-12z = -76 3(4x-3y+4z = 18) => 12x-9y+12z = 54 Adding the above: 24x-y = -22 thus eliminating z 2(12x-11y = 10) => 24x-22y = 20 1(24x-y = -22) => 24x-y = -22 Subtracting the above: -21y = 42 thus eliminating x If: -21y = 42 then y = -2 So by substitution: x = -1, y = -2 and z = 4 Check: (2*-1)-(5*-2)+(2*4) = 16 Check: (3*-1)+(2*-2)-(3*4) = -19 Check: (4*-1)-(3*-2)+(4*4) = 18

Numbers are divisible by 6 if they are even and also divisible by 3. examples are 6,12,18,24,30,36,60,54,...... examples as algebric expressions 18xy+12z+6y-a,where a is divisible by 6 i.e 6,12,18...

Related questions

-3z+17+12z = 11 9z = -6 z = -2/3

6z + 28 = 12z + 10 18 = 6z 3 = z

6z+28=12z+10 6z-12z=10-28 addition property of equality. -6z=-18 simplification z=3 multiplication property of equality.

There are three variables in the equation. In order to find numbers for all of them,you need three separate independent equations.As it is now, the graph of that equation is a line in 3-dimensional space, andevery point on the line is a 'solution' to the equation. We don't have to tell youhow many points there are on a line, do we ?

12z-5 = -41 12z = -41+5 12z = -36 z = -3

(z - 6)(z - 6)

-3

24z+4 or 6(4z+1)

divide each side by 12; Z=9

-99 = 12z - 3(6)zSimplifying the expression, we have:-99 = 12z - 18z = -6zDivide by -6:z = 16.5Or, if you meant 3 6 as the number, we have:-99 = 12z - 36zSimplify:-99 = -24zDivide by -24:z = 4.125

It is a quadratic expression and is (2z+3)(6z-1) when factored

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z